2004
DOI: 10.1080/13803390490510680
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Impairment in Executive Functioning: Updating, Inhibition, Shifting, and Access

Abstract: Miyake, Friedman, Emerson, Witzki, Howerter and Wager (2000) have argued that the central executive is fractionated consisting of at least three separable component processes: updating, shifting, and inhibition. The Wisconsin Card Sort Test, random letter generation, Brooks spatial sequences, reading and computation span, word fluency, and a measure of dual task performance were administered to 95 individuals aged between 20 and 81, average age 41.89. The executive measures were factor analyzed, using the obli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
442
4
30

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 538 publications
(495 citation statements)
references
References 35 publications
19
442
4
30
Order By: Relevance
“…We aimed to use "pure" measures of each of the three postulated executive functions (updating, shifting and inhibition), and provide further clarification of the nature of executive deficits in ecstasy users. In a study of cognitive ageing, Fisk and Sharp (2004) provided further support for Miyake et al's model. Factor analysis revealed that certain tasks loaded on each of the three components identified by Miyake et al, but there was also a distinct executive function loading on another factor, which Fisk and Sharp termed access to long-term memory (although age was not a significant predictor of performance on "access" tasks).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…We aimed to use "pure" measures of each of the three postulated executive functions (updating, shifting and inhibition), and provide further clarification of the nature of executive deficits in ecstasy users. In a study of cognitive ageing, Fisk and Sharp (2004) provided further support for Miyake et al's model. Factor analysis revealed that certain tasks loaded on each of the three components identified by Miyake et al, but there was also a distinct executive function loading on another factor, which Fisk and Sharp termed access to long-term memory (although age was not a significant predictor of performance on "access" tasks).…”
Section: Introductionmentioning
confidence: 67%
“…Consistent with this proposition, Verdejo-Garcia et al (2005) found that ecstasy use was an important contributory factor in deficits in working memory updating among a clinical sample of poly-substance abusers. Similarly research from our own laboratory demonstrates that ecstasy users are impaired on tasks such as computation span , which is also known to load on the updating executive function (Fisk & Sharp, 2004). Equally it appears that tests sensitive to the shifting and inhibition elements do not appear to be as consistently susceptible to the effects of ecstasy (e.g.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, we used a self report measure of executive functioning rather than laboratory based measures. It might have been desirable to incorporate laboratory based tests of executive functioning, however, recent conceptualisations of executive functioning have emphasised the non unitary nature of these processes, identifying four or more separable processes: updating, inhibition, switching, and access to semantic memory (Fisk & Sharp, 2004;Miyake et al, 2000) each with a number of specific measures. Furthermore, ecstasy/polydrug users appear to be differentially affected on each of these .…”
Section: Discussionmentioning
confidence: 99%